On the asymmetry of eddy-induced surface chlorophyll anomalies in the southeastern Pacific: The role of eddy-Ekman pumping. (February 2016) - He, Qingyou; Zhan, Haigang; Cai, Shuqun; Zha, Guozhen
Highlights: Chlorophyll anomalies formed by eddy stirring and eddy-Ekman pumping distinguished. Eddy-Ekman pumping dominates the asymmetry of chlorophyll anomalies within eddies. Eddy-Ekman pumping may represent important sources of new production in winter. Abstract: Mesoscale eddies are ubiquitous features of the World Ocean and have dramatic impacts on the distribution of surface chlorophyll (CHL). It has been reported that CHL anomalies (CHLAs) associated with eddies are dominantly controlled by eddy stirring on a global scale. However, the resultant CHLAs show asymmetric dipoles, indicating that other mechanisms may also play important roles. By analyzing the composite averages of CHLAs associated with 28, 293 individual eddies in the southeastern Pacific from 1998 to 2011, we showed that the asymmetry of the CHLAs is mainly attributed to eddy-Ekman pumping. Eddy-Ekman pumping could generate a positive (negative) CHL monopole centered on the core of an anticyclonic (cyclonic) eddy, and the superposition of such a monopole would modify the dipole structure of CHLAs formed by eddy stirring thus result in an asymmetric pattern. The asymmetry exhibits pronounced seasonality, depending on the relative contributions of eddy stirring and eddy-Ekman pumping. In austral winter, the CHL enrichment brought by the upwelling in anticyclonic eddies is more dominant than the CHL diminishment forced by the downwelling in cyclonic eddies, suggesting that eddy-Ekman pumping may represent important sources of new production during this period.